2009
DOI: 10.1137/070693461
|View full text |Cite
|
Sign up to set email alerts
|

A Polynomial Predictor-Corrector Trust-Region Algorithm for Linear Programming

Abstract: In this paper we present a scaling-invariant, interior-point, predictor-corrector type algorithm for linear programming (LP) whose iteration-complexity is polynomially bounded by the dimension and the logarithm of a certain condition number of the LP constraint matrix. At the predictor stage, the algorithm either takes the step along the standard affine scaling (AS) direction or a new trust-region type direction, whose construction depends on a scaling-invariant bipartition of the variables determined by the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Thus, Monteiro and Tsuchiya's question can be rephrased as to whether there exists an exact LP algorithm with running time poly(n, m, logχ * A ). Substantial progress on this question was made in the followup works [MT05,LMT09]. [MT05] showed that the number of iterations of the MTY predictor-corrector algorithm [MTY93] can get from µ 0 > 0 to η > 0 on the central path in O n 3.5 logχ * + min{n 2 log log(µ 0 /η), log(µ 0 /η)} iterations.…”
Section: The Question Of Scale Invariance Andχ *mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Monteiro and Tsuchiya's question can be rephrased as to whether there exists an exact LP algorithm with running time poly(n, m, logχ * A ). Substantial progress on this question was made in the followup works [MT05,LMT09]. [MT05] showed that the number of iterations of the MTY predictor-corrector algorithm [MTY93] can get from µ 0 > 0 to η > 0 on the central path in O n 3.5 logχ * + min{n 2 log log(µ 0 /η), log(µ 0 /η)} iterations.…”
Section: The Question Of Scale Invariance Andχ *mentioning
confidence: 99%
“…Moreover, on the "straight" parts of the path, the rate of progress amplifies geometrically, thus attaining a log log convergence on these parts. Subsequently [LMT09] developed an affine invariant trust region step, which traverses the full path in O(n 3.5 log(χ * A + n)) iterations. However, each iteration is weakly polynomial in b and c. The question of developing an LP algorithm with complexity bound poly(n, m, logχ * A ) thus remained open.…”
Section: The Question Of Scale Invariance Andχ *mentioning
confidence: 99%
“…Thus, Monteiro and Tsuchiya's question can be rephrased as to whether there exists an exact LP algorithm with running time poly(n, m, log χ * A ). Substantial progress on this question was made in the followup works [MT05,LMT09]. [MT05] showed that the number of iterations of the MTY predictor-corrector algorithm [MTY93] can get from µ 0 > 0 to η > 0 on the central path in O n 3.5 log χ * + min{n 2 log log(µ 0 /η), log(µ 0 /η)} iterations.…”
Section: The Question Of Scale Invariance and χ *mentioning
confidence: 99%
“…Moreover, on the "straight" parts of the path, the rate of progress amplifies geometrically, thus attaining a log log convergence on these parts. Subsequently [LMT09] developed an affine invariant trust region step, which traverses the full path in O(n 3.5 log( χ * A + n)) iterations. However, each iteration is weakly polynomial in b and c. The question of developing an LP algorithm with complexity bound poly(n, m, log χ * A ) thus remained open.…”
Section: The Question Of Scale Invariance and χ *mentioning
confidence: 99%
“…Lan, Monteiro and Tsuchiya [22] gave a scaling invariant trust region IPM taking O(n 3.5 log( χ * A + n)) iterations. Here, χ *…”
Section: Introductionmentioning
confidence: 99%